The genus Folsomides Stach (Collembola, Isotomidae) in Kermanshah Province (W Iran) with the description of two new species - Arbea, Javier I.; Kahrarian, Morteza (Zootaxa, 2015)
The genus Folsomides Stach, 1922 is represented by four species in the Iranian fauna, two of which are new to the science. Folsomides halshinicus sp. nov. and Folsomides subvinosus sp. nov. are found in Kermanshah Province (Western Iran). The new species belong to the Folsomides angularis (Axelson, 1905) group and they are distinguishable from other congeneric species by the macrochaetotaxy (11/22233 macrochaetae on thoracic II to abdominal V tergites) and the number of chaetae on dens. A table with the diagnostic characters for the identification of Iranian species of Folsomides is given. Some figures of F.vinosus Fjellberg, 1993 from Canary Island was given after study of type specimens.